نفي الفرق وعلاقته بالقياس (دراسة تطبيقية في كتاب العزيز شرح الوجيز للرافعي): Deniying the Difference and Its Relation with Mensuration (Applied Study in the Book al-`Azīz Syarḥ al-Wajīz by al-Rāfi'ī) - Eko Misbahuddin Hasibuan (البصيرة: مجلة الدراسات الإسلامية, 2022)
This research aims to clafiry the relation between deniying the difference with mensuration, by mentioning the definition of deniying the difference and mensuration by scholars of the principles of jurisprudence. It appears by looking between the two concepts that there is a close relationship between them. This research is based on the descriptive, analytical and deductive method, because it combine the theory and practice, and attempt to deduce the type of relationship between measurement and the negation of the difference from some jurisprudential applications in the book of Al-Aziz Syarh al-Wajiz By Imam al-Rafi'i. The research reveals important results, including: (First) To negate the difference is a kind of analogy, it may be a clear or hidden analogy, according to the obligations or the common meanings between the branch and the original of matter. (Second) It is necessary to investigate the causes and causes affecting the appending of the branch to the original, so that the researcher can judge whether the difference is proven or not. (Third) Knowing the aspect of denying the difference between the two issues, that apparent difference in the ruling, and its obligations, requires looking at the books of the schools of thought, then comparing them to find out what is most likely between the correctness of the appendix or its inaccuracy, it based on the evidence mentioned by each team strength and weakness.